RESPON TANAMAN DAHLIA (Dahlia pinnata) PADA BERBAGAI MACAM MEDIA TANAM DAN PUPUK ORGANIK CAIR - Libria Widiastuti (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2019)
Dahlias have a high potential for development in West Sumatra Province. This is based on a number of cities in West Sumatra such as Bukit Tinggi and Agam Regency which have designated themselves as "The City of Dahlia" to develop the potential of this biological resource. The objectives to be achieved in this study are: (1) to determine the effect of various types of planting media that are good for growth and quality of flowers on dahlia plants. (2) to determine the effect of various types of liquid organic fertilizer which is good for growth and flower quality in dahlia plants. (3) to determine the interaction of various types of planting media and liquid organic fertilizer types on the growth and quality of flowers in seruni plants. This research was conducted from July to October 2019 in Kudu Baki Sukoharjo, Central Java, with a height of 100 meters above sea level. The experiments were arranged in a Completely Randomized Design (CRD), which consisted of two factors and three replications. Kinds of Planting Media (M) consist of 4 levels, namely: top soil, husk charcoal, bamboo leaf humus, and fern. Liquid Organic Fertilizer (P) consists of 3 levels, namely: IN Grow, GDM, and Grow more. The results showed that the treatment of organic fertilizer in Grow Grow and rice husk charcoal growing media showed the highest results significantly for all observations, namely plant height, leaf area, flower appearance, flower diameter, tuber diameter and harvest age. Growmore fertilizer treatment and top soil planting media showed the lowest results significantly for all observed parameters, namely plant height, leaf area, flower appearance, harvest age, flower diameter and plant shelf life. There was no interaction between the treatment types of the planting media and the types of liquid organic fertilizer on all observational parameters.